Revealing Students’ and Teachers’ Perceptions of Challenges and Strategies in Arabic Reading Comprehension - Othman, Osama (AUC Knowledge Fountain, 2025)
This thesis investigates the perceptions of Arabic as a Foreign Language (AFL) students and teachers regarding the influence of eight textual features on reading comprehension. These features are: vowelization, word patterns, roots, vocabulary, case endings, word order, punctuation marks, and text organization. It also investigates reading comprehension strategies employed by both groups to overcome comprehension challenges associated with these features. Data were collected from 102 AFL students and 26 AFL teachers through questionnaires, and semi-structured interviews were conducted with 6 students and 11 teachers. Results revealed that students generally rated the influence of these features more highly than teachers. The disparity could be attributed to the text types students read independently (authentic texts) compared to those used in classroom settings (textbooks, adapted materials). All coping strategies were rated by students as either ‘usually’ or ‘sometimes’ employed with reference material use and bottom decoding skills emerging as most frequently top employed. Teachers reported frequently utilizing comprehension checks, emphasizing bottom-up decoding skills, and incorporating pre-reading strategies to help students overcome challenges associated with textual features. Qualitative data, through interviews, provided valuable insights into the specific challenges faced by students and the strategies employed by students and teachers based on their actual experiences. A deeper understanding of these perceptions highlights the importance of conducting students’ needs analysis and adapting instruction to foster learners' autonomy.